Production Scheduling Optimization Using The Campbell Dudek Smith (CDS) Method to Minimize Makespan in A Flow Shop Manufacturing System - Venantius Almas Mario; Achmad Alfian; Heri Setiawan (Ann Publisher, 2026)
Background: Production scheduling plays a crucial role in improving manufacturing system efficiency, particularly in flow shop environments where jobs must follow the same processing sequence across multiple machines. At CV. Sinar Surya, the production scheduling for lathe machines is still conducted manually based on operator experience, resulting in high machine idle time, low machine utilization, and prolonged makespan. This condition causes inefficiencies in production processes and delays in order completion. Therefore, an effective scheduling method is required to optimize the production sequence and improve operational efficiency. Aim: This study aims to optimize production scheduling in a flow shop manufacturing system by applying the Campbell-Dudek-Smith (CDS) method to minimize makespan and reduce lathe machine idle time. Methods: The research was conducted at CV. Sinar Surya Palembang uses a quantitative approach. Data were collected through direct observation, interviews with production staff, and company documentation. The collected data include processing time for each job, production sequences, machine working hours, and existing production schedules. The CDS heuristic method was applied by transforming the multi-machine flow shop problem into several two-machine subproblems, which were then solved using Johnson’s rule to determine the optimal job sequence. Results: The existing production schedule yielded a makespan of 163 minutes and a total machine idle time of 140 minutes. After applying the CDS method, the optimal job sequence obtained was J4 - J5 - J3 - J1 - J2, which reduced the makespan to 147 minutes and decreased total idle time to 95 minutes. This represents a 16-minute reduction in makespan (approximately 9.8%), indicating improved production efficiency. Conclusion: The implementation of the CDS method improves production scheduling efficiency in a flow shop manufacturing system by generating a more optimal job sequence, reducing makespan, and machine idle time. Implication: The findings suggest that the CDS method can be an effective scheduling approach for manufacturing companies using flow shop systems, particularly for improving machine utilization, reducing production delays, and supporting better production planning and decision-making.